2002
DOI: 10.1023/b:glyc.0000014093.23509.92
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of galectin-1 in skeletal muscle determination, differentiation and regeneration

Abstract: The dogma that a cell is rigidly committed to one tissue type has been heavily challenged over the past few years with numerous reports of transdifferentiation of cells between different lineages. Cells capable of entering lineages other than that of their tissue of origin have been identified in several diverse tissues. Recently we have focussed on a non-committed myogenic cell within the dermis that is capable, under certain conditions, of expressing muscle specific markers and even fusing to the terminally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 34 publications
3
52
0
5
Order By: Relevance
“…Interestingly, enhanced expression of ␣7␤1 integrin has been shown to prevent the onset of the dystrophic process in the mouse model for Duchenne muscular dystrophy (Burkin et al, 2001). These data suggest a role for galectin-1 in muscle differentiation, and this role is substantiated by several lines of evidence that show an increased fusion of myoblasts to the multinucleate muscle fiber stage in vitro in the presence of the lectin (Gartner and Podleski, 1975;Nowak et al, 1976;Watt et al, 2004). In both chick (Nowak et al, 1976) and mouse (Poirier et al, 1992) skeletal muscle development, the level of galectin-1 is highest during the maximum stage of myoblast fusion, implicating a role for the molecule in the myoblast recognition-fusion process (Nowak et al, 1976).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, enhanced expression of ␣7␤1 integrin has been shown to prevent the onset of the dystrophic process in the mouse model for Duchenne muscular dystrophy (Burkin et al, 2001). These data suggest a role for galectin-1 in muscle differentiation, and this role is substantiated by several lines of evidence that show an increased fusion of myoblasts to the multinucleate muscle fiber stage in vitro in the presence of the lectin (Gartner and Podleski, 1975;Nowak et al, 1976;Watt et al, 2004). In both chick (Nowak et al, 1976) and mouse (Poirier et al, 1992) skeletal muscle development, the level of galectin-1 is highest during the maximum stage of myoblast fusion, implicating a role for the molecule in the myoblast recognition-fusion process (Nowak et al, 1976).…”
Section: Introductionmentioning
confidence: 85%
“…However, a detailed examination of skeletal muscle of the null mouse had never been undertaken. Our preliminary data suggested that regeneration of skeletal muscle in response to trauma is somewhat attenuated in the galectin-1 null mouse (Watt et al, 2004). In the light of these preliminary data, we undertook a more detailed study of galectin-1 null muscle by studying the response of galectin-1 null myoblasts in culture, the development of galectin-1 null muscle, and lastly the regenerative response of this muscle to traumatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…43 LGALS1 enhances the fusion of myoblasts in myotubes and this explains why galectin-1 is expressed at high levels when maximal cell fusion occurs during muscle development. 44 Bridgingintegrator protein-1 isoform BIN1112A (BIN1) is a nucleocytoplasmic adaptor protein that interacts at the Myc box region at the amino terminus of the c-myc protein. Cells overexpressing human BIN1 grow more slowly than control myoblasts, and they differentiate more rapidly when depleted of growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…LGALS1 appears to play a role in a broad array of cell functions, including cell adhesion, migration, apoptosis, differentiation, nerve and muscle regeneration, and immunoregulation (Almkvist and Karlsson, 2004;Watt et al, 2004;Jiang et al, 2005;Liu, 2005). LGALS1 has also been associated with an anti-inflammatory function (Chung et al, 2000;La et al, 2003).…”
Section: Activity Of Immune Response/inflammationrelated Genes Duringmentioning
confidence: 99%